Assessment of Knowledge of Nurses in Providing Psychosocial Care for Mothers with Sickle Cell Child in Osun State Nigeria - Adams Olatayo Omolola; Aderonke Bosede Adesuyi; Basirat Temitope Omolola; Tolulope Kosemani (Babali Health, 2020)
Introduction: This descriptive study is designed to assess the knowledge of nurses in providing psychosocial care for mothers with sickle cell diseases child in Osun State Nigeria. Methods: Nurses working in the two teaching hospitals were used. Simple self-designed questionnaire was adopted, two hundred (200) respondents primarily the nurses were used in the research study. The questionnaire has three sections: the demographic variables, Knowledge of nurses on use of psychosocial care and mothers’ knowledge on care of child with Sickle Cell Disease (SCD). The data were collected and analysed using a descriptive statistics of percentage and frequency. Results: The results revealed that there is a need to improve nursing skills on psychosocial care among the nurses. The current nursing practices with regard to psychosocial care needs to be reviewed and upgraded so as to give a desired outcome. 46.5% of the nurses reported that mothers do not have confidence in the skills of nurses in providing psychosocial care, 43.5% have confidence in the skills of nurses while 10% were undecided. Besides, 90% of nurses agreed that there is a need for continuous retraining of nurses in providing a positive outcome of psychosocial care while only 10% do not agreed. Conclusion: It was concluded that psychosocial care plays an important role in managing patients with SCD, hence, there is a need to retrain nurses on standard method of psychosocial care.